Community perspectives to inform the development of a radio program to destigmatize mental illness in rural Uganda: a qualitative study - Yang Jae Lee; Brandon Fickling; Micah Goode; AnnaBelle Gallaher; Rauben Kazungu; Paul Coffin; Maya Abdel-Megid; Frederick Isabirye; Ibrahim Ssekalo; Scholastic Ashaba; Robert Rosenheck; Alexander C Tsai (Inishmore Laser Scientific Publishing Ltd, 2024)
# Background The stigma attached to mental illness impedes diagnosis, treatment, and access to care for people with mental illness. Scalable interventions are needed to enhance attitudes towards seeking treatment, foster community support, and promote acceptance of individuals experiencing mental illness. We worked with community health workers in the Busoga region of eastern Uganda to develop a radio program aimed at reducing mental illness stigma. We piloted the radio program in focus groups, purposively sampling people with families affected by mental illness and people with families unaffected by mental illness, to understand their perspectives about the program's acceptability and potential effectiveness. # Methods The 45-minute radio program was adapted from a previously studied community-led theater intervention, produced by community health workers, that demonstrated an individual's recovery from mental illness. Afterward, we conducted 2 focus group discussions, each involving six participants: n=12; and 17 one-on-one, in-depth interviews. We employed the framework method to inductively identify themes and sub-themes. # Results Participants reported greater understanding of causes of mental illness, treatment options, and greater acceptance of those with mental illness as a result of listening to the program. # Conclusions This radio program intervention showed potential to change healthcare seeking behavior for mental illness and to decrease mental illness stigma in rural Uganda. Further investigation is needed to assess the broader applicability of this approach.